2021
DOI: 10.3389/fmicb.2021.643422
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vaginal Microbiota Dysbiosis in Gynecological Diseases and the Potential Interventions

Abstract: Vaginal microbiota dysbiosis, characterized by the loss of Lactobacillus dominance and increase of microbial diversity, is closely related to gynecological diseases; thus, intervention on microbiota composition is significant and promising in the treatment of gynecological diseases. Currently, antibiotics and/or probiotics are the mainstay of treatment, which show favorable therapeutic effects but also bring problems such as drug resistance and high recurrence. In this review, we discuss the role of vaginal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 108 publications
0
42
0
15
Order By: Relevance
“…It should be emphasized that the vagino–uterine microbiota and its dysbiosis may influence the pathogenesis of several gynecological infectious and non-infectious illnesses [ 18 , 20 , 102 ], including gynecologic cancers [ 103 ]. Recently, it was observed that dysbiosis of the vaginal microbiome may be involved in recurrent implantation failure (RIF) at various stages, such as formation of gametes, implantation, and delivery [ 18 , 104 ].…”
Section: Vaginal and Endometrial Microbiome (Microbiota) Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be emphasized that the vagino–uterine microbiota and its dysbiosis may influence the pathogenesis of several gynecological infectious and non-infectious illnesses [ 18 , 20 , 102 ], including gynecologic cancers [ 103 ]. Recently, it was observed that dysbiosis of the vaginal microbiome may be involved in recurrent implantation failure (RIF) at various stages, such as formation of gametes, implantation, and delivery [ 18 , 104 ].…”
Section: Vaginal and Endometrial Microbiome (Microbiota) Disturbancesmentioning
confidence: 99%
“…Uterine anatomical abnormalities (bicornal uterus, uterine septa, myomas, endometrial polyps, intrauterine adhesions) [8] immunological (HLA, NK cells, TK cells) [9,10] biomolecular (p53, LIF) [11][12][13][14] glycodelin-A [15][16][17] infection [18][19][20] Table 1. Cont.…”
Section: Risk Factors Of Rif Referencesmentioning
confidence: 99%
“…2,6,7 Vaginal microbiota dysbiosis, characterized by the loss of lactobacilli dominance and increase of microbial diversity, is closely related to gynecological diseases. 8 Among these, bacterial vaginosis (BV) is associated with an excessive growth of diverse, predominantly anaerobic bacteria including Gardnerella, Prevotella, Atopobium, Mobiluncus, and Sneathia, 9 as well as a decrease in lactic acid and hydrogen peroxide concentration resulting in an increase in vaginal pH. 10 BV is often diagnosed by a gramstain based Nugent score (NS) of 7-10, 11 as well as via Amsel's criteria, point-of-care, 12 and more recently, molecular tests.…”
Section: Introductionmentioning
confidence: 99%
“…FMT contains the microbiome, which is critical in maintaining homeostasis and health. Microbiota dysbiosis is also responsible for gynecological cancer [ 263 , 264 , 265 ]. Epidemiological studies indicate that the urogenital microbiota dysbiosis is implied in gynecological cancers, particularly cervical cancer [ 263 , 264 , 266 ].…”
Section: Gut Microbiota and Cancer Therapy Efficacymentioning
confidence: 99%
“…Microbiota dysbiosis is also responsible for gynecological cancer [ 263 , 264 , 265 ]. Epidemiological studies indicate that the urogenital microbiota dysbiosis is implied in gynecological cancers, particularly cervical cancer [ 263 , 264 , 266 ]. Probiotics or microbiota transplant seems to be effective in improving responsiveness to treatment of gynecological cancer [ 263 , 267 , 268 ].…”
Section: Gut Microbiota and Cancer Therapy Efficacymentioning
confidence: 99%